Ketahanan Badan Usaha Milik Desa : Peningkatan Kapasitas dalam Analisis Bisnis dan Pelaporan Keuangan - Mahmud, Amir; Susilowati, Nurdian; Ridloah, Siti; Santoso, Arif; Sari, Puji Novita (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2025)
Village-Owned Enterprises (BUMDes) play a strategic role in enhancing village economic independence, but they still face challenges in management and accounting governance. BUMDes Kaya Guna in Kalisidi Village, Semarang Regency, is one example facing issues with business management and financial record-keeping, which are still done manually. This community service program aims to strengthen the business and financial management capabilities of the BUMDes Kaya Guna board through the Participatory Rural Appraisal (PRA) approach. Activities were conducted in the form of counseling, training, and mentoring, focusing on Break-Even Point (BEP) analysis, Return on Investment (RoI), Payback Period (PP), basic accounting concepts, and the implementation of computerized accounting based on SAK ETAP. The results of the activities showed an improvement in participants' understanding of how to prepare business feasibility analyses and more systematic financial reports. Positive feedback from the management and the Village Head of Kalisidi underscored the program's benefits in strengthening healthy, transparent, and accountable business management. The evaluation also identified challenges such as technological limitations and initial lack of understanding, which were addressed through intensive mentoring. Overall, the program successfully enhanced the managerial and accounting capacities of the BUMDes Kaya Guna management team and supported the realization of sustainable BUMDes governance.